CAMBODIAN TEACHERS' READINESS FOR ONLINE TEACHING: PERCEPTIONS AND CHALLENGES - Be, Borey (Asosiasi Dosen Perguruan Tinggi Islam, 2024)
This study gauges the readiness of Cambodian teachers for Online Teaching and Learning (OTL) in higher education institutions (HEIs). A quantitative design was utilized, including 140 teachers who participated in an online survey consisting of 29 question items. The research found that teachers certainly assessed their OTL competencies favorably, with mean scores between 3.63 and 3.73 across diverse skills. The research found that teaching experience has a positive effect on readiness for online teaching and learning, especially concerning pedagogical strategies and self-efficacy in digital settings. Nonetheless, the association was less significant for technological knowledge. TPACK and perceived institutional support emerged as significant predictors of teachers' readiness. This research enhances comprehension of the complexity surrounding teacher readiness for OTL in Cambodia. The recommendation is to address shortcomings in technological expertise and to improve institutional support by implementing comprehensive professional development that is tailored to the needs of teachers.